To find the value of x that makes the equation true, we need to solve for x.
Distribute -5 to the terms inside the parentheses:
-10x + 15 + 4x = -3x + 6
Combine like terms:
-6x + 15 = -3x + 6
Move all the terms with x to one side of the equation by adding 3x to both sides:
-6x + 3x + 15 = 6
Combine like terms:
-3x + 15 = 6
Move the constant term to the other side by subtracting 15 from both sides:
-3x = -9
Finally, solve for x by dividing both sides by -3:
x = (-9) / (-3)
x = 3
Therefore, the value of x that makes the equation true is 3.
Math Equation Response Question
What is the value of x that makes this equation true?
-5(2x-3)+4x=-3x+6
1 answer